47.3k views
3 votes
Rewrite the function by completing the square.
f(x) = x² + 12x - 69​

User Marilu
by
4.7k points

1 Answer

3 votes

Final answer:

To rewrite the function by completing the square, follow these steps: Take the coefficient of the x-term (12) divided by 2, then square it.

Step-by-step explanation:

To rewrite the function by completing the square, follow these steps:

  1. Take the coefficient of the x-term (12) divided by 2, then square it: (12/2)^2 = 36.
  2. Add the result from step 1 to both sides of the equation: x^2 + 12x + 36 - 69 = 36 - 69.
  3. Simplify: x^2 + 12x + 36 - 69 = -33.
  4. Factor the perfect square trinomial: (x + 6)^2 = -33.
  5. Take the square root of both sides: x + 6 = ±√(-33).
  6. Solve for x: x = -6 ± √(-33).

User LRutten
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.